2011
DOI: 10.1093/ecam/nep052
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Salacia reticulata on Obesity and Metabolic Disorders in TSOD Mice

Abstract: The extracts of Salacia reticulata (Salacia extract), a plant that has been used for the treatment of early diabetes, rheumatism and gonorrhea in Ayurveda, have been shown to have an anti-obesity effect and suppress hyperglycemia. In this study, the effects of Salacia extract on various symptoms of metabolic disorder were investigated and compared using these TSOD mice and non-obese TSNO mice. Body weight, food intake, plasma biochemistry, visceral and subcutaneous fat (X-ray and CT), glucose tolerance, blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 26 publications
3
30
2
1
Order By: Relevance
“…Generally, the observed levels of ALT and AST found in our controls and orally treated groups are lower than what is observed in other studies, [9][10][11][12] but we ascribe the differences in absolute values to differences in the experimental procedures and mouse strains.…”
Section: Discussioncontrasting
confidence: 89%
“…Generally, the observed levels of ALT and AST found in our controls and orally treated groups are lower than what is observed in other studies, [9][10][11][12] but we ascribe the differences in absolute values to differences in the experimental procedures and mouse strains.…”
Section: Discussioncontrasting
confidence: 89%
“…Data represent the mean ± SD values (n = 9-10). *Significantly different from the TSOD mice control at P \ 0.05 Also, we have reported that S. reticulata showed usefulness against various metabolic abnormalities including obesity in a study using TSOD mice [18]. However, in the previous study, S. reticulata also showed a suppressing effect on body weight increase and fat accumulation in the TSNO mice used as controls, suggesting that the effects might have indicated toxic changes due to overdosage of S. reticulata.…”
Section: Discussionmentioning
confidence: 73%
“…The following mechanisms of action for these various effects of Salacia family plants have been reported: inhibition of a-glucosidase in the small intestine [8], activation of peroxisome proliferator-activated receptor-alpha (PPARa) [7], inhibition of angiotensin II type 1 receptor (AT 1 ) [9], inhibition of aldose reductase [10], inhibition of gluconeogenic fructose-1,6-bisphosphatase (FBP) [4], and increased oxygen consumption [11]. Using Tsumura Suzuki obesity diabetes (TSOD) mice [12][13][14][15][16][17] (a spontaneously obese type II diabetes mouse model), we have already clarified that S. reticulata shows the following effects: suppression of body weight increase and visceral and subcutaneous fat accumulation, improvement of glucose/lipid metabolism, suppression of blood pressure increase, and prevention of peripheral nerve impairment, and reported that S. reticulata is a promising material showing effects not only on each individual metabolic disease but also on various symptoms of the entire metabolic syndrome [18]. In that experiment, however, S. reticulata also showed a strong suppressing effect on body weight increase and a suppressing effect on visceral and subcutaneous fat accumulation in the Tsumura Suzuki non-obese (TSNO) mice, which are reference animals that display no metabolic diseases such as obesity and type II diabetes, suggesting that the effects might have been toxic changes due to overdosage of S. reticulata.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of the isolated compounds from P. campestris confirmed the results obtained with STAMP method. P. campestris was chosen for the MIC experiment because it contains substances named quinonemethide triterpenoids, such as maytenin and netzahualcoyone, that are chemotaxonomic markers of the Celastraceae family, and that exhibit a myriad of biological activities [15,16]. The results we obtained with the powdered plant material of P. campestris using the STAMP method and the results of maytenin and netzahualcoyone using the MIC method were similar and showed greatest antimicrobial activity against S. aureus, followed by C. parapsilosis and C. albicans.…”
Section: Discussionmentioning
confidence: 99%